A pilot study of social inclusion and quality of life for parents of children with autism spectrum disorder. Issue 1 (2nd January 2018) - Due, Clemence; Goodwin Smith, Ian; Allen, Penny; Button, Eleanor; Cheek, Colleen; Quarmby, Lyndsay; Stephens, Miranda; Paku, Sofia; Ferguson, Sarah; Fordyce, Kathryn
ABSTRACT: Background Access to both childcare and early intervention for pre-school children with autism spectrum disorder (ASD) can be difficult for parents or carers and may impact on parental social inclusion and wellbeing. There is limited research investigating how specialist centres offering both services may impact on parental outcomes. Method Parents whose children were attending such a specialised childcare setting in two states in Australia (Tasmania and South Australia) were invited to participate in a mixed-methods study investigating quality of life (Qol), social inclusion and perceptions of the centres. Results Parents had typically low levels of QoL but reported a range of benefits from receiving services, including increased levels of community participation and increased competence and confidence in themselves as parents. Conclusions Childcare centres offering specialist multi-disciplinary early intervention and parental support are valued by parents and assist with social inclusion.